Pressure changes at spinal epidural and intracranial regions in fresh cadavers during full endoscopic lumbar spine surgery with continuous irrigation - Metehan Ozturk; Ilyas Dolas; Ali Guven Yorukoglu; Duygu Dolen; Tugrul Cem Unal; Dogukan Ozler; Eren Andıc; Duran Sahin; Cafer Ikbal Gulsever; Musa Samet Ozata; Ceyhun Kucuk; Halit Cakir; et al. (Journal of Orthopaedic Surgery and Research)
Abstract Purpose Despite the benefits over classical microdiscectomy, Full endoscopic lumbar discectomy (FELD) has been associated with complications attributed to changes in intracranial pressure (ICP). This study aimed to assess intracranial and epidural pressure changes at different spinal levels induced by continuous irrigation during FELD. Materials and methods Eight fresh cadavers (ages 41–78) devoid of cranial or spinal trauma were utilized. RIWOspine and Joimax endoscopic systems were used, with ICP measured via an intraventricular catheter placed at Kocher’s point. Pressure measurements were taken at lumbar, thoracic, cervical, and intracranial levels using 18G-Tuohy needles connected to digital manometers. Measurements were recorded under different irrigation modes (Arthro 120-mmHg, Arthro 195-mmHg, Spine-50 mmHg) and analyzed using repeated measures ANOVA. Results The highest pressure values were observed with Arthro-mode at 195-mmHg, followed by Arthro-mode at 120-mmHg, and the lowest values with Spine-mode. Joimax endoscopes showed higher pressure values than RIWOspine endoscopes, particularly in the lumbar and thoracic regions. Cranial pressure increases were immediate and significant after irrigation initiation, whereas thoracic and cervical pressures increased more slowly. The pressure increase model in the thoracic and cervical regions was not observed in repeated measurements, indicating possible adaptation or relief mechanisms. The average pressure difference across all points was 29.74 mmHg, with the most significant difference in the lumbar region (35.69 mmHg). Conclusion Continuous irrigation during FELD significantly impacts epidural and intracranial pressures. The choice of endoscope and irrigation mode is crucial in minimizing these pressure changes. Proper management can prevent potential complications associated with increased pressure levels.